Evaluation of postoperative complications after mandibular third molar surgery with the use of platelet-rich fibrin: a systematic review and meta-analysis. Issue 9 (September 2017) - Canellas, J.V. dos S.; Ritto, F.G.; Medeiros, P.J.D.
Abstract: The current literature was reviewed to analyze the effects of platelet-rich fibrin (PRF) on postoperative complications after mandibular third molar surgery (pain, alveolar osteitis, swelling, and bone healing). A comprehensive literature search was performed up to 2016 in the PubMed/MEDLINE, Cochrane Library, LILACS, and ScienceDirect databases and the grey literature. Additional records were identified through manual and reference searches. The full-text articles of potentially relevant studies were reviewed; only randomized clinical trials were included. Two review authors assessed the risk of bias independently. A total of 1430 publications were evaluated, of which seven were selected for qualitative analysis and two for quantitative analysis. A meta-analysis was performed only for alveolar osteitis, due to the considerable heterogeneity among studies for the other outcome variables. There were 485 extractions (243 test, 242 control) in 280 patients. PRF appeared to accelerate healing in mandibular third molar surgery, reducing postoperative pain and swelling. Quantitative analysis showed a decrease in prevalence of alveolar osteitis (odds ratio 0.31, 95% confidence interval 0.13–0.77, Z  = 2.54, P  = 0.01). Although more clinical trials of a better design and with larger samples are necessary to allow definitive conclusions to be drawn, PRF is a potentially useful biomaterial.